In Search of a Deferred Prosecution Agreement Model for Effective Anti-Corruption Framework in Indonesia - Febby Mutiara Nelson (Hasanuddin Law Review, 2022)
To help reduce the corruption in the criminal justice system, Indonesia should consider implementing a Deferred Prosecution Agreement (DPA) mechanism. DPA would not only aiming for punishment to corporations, especially in special and general deterrence, but also could accommodate in returning state assets from perpetrators. Indonesia could learn from the DPA models applied in the U.K. and U.S., as well as the proposed model in Australia. DPA models could be noteworthy in making the criminal justice process more effective, efficient, and less time-consuming, as well as resolving the problems of significant caseloads and ongoing corruption.